Evaluasi Resistensi Terhadap Metoksifenozida Pada Spodoptera Exigua di Jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The objective of this research was to know the resistance level of beet armyworm Spodoptera exigua to methoxyfenozide. The larvae were collected from the shallot production areas in the districts ofNganjuk (East Java), Bantul dan Kulonprogo (Yogyakarta Special Territory) and Brebes (Central Java). The bioassay usedjirst instars of S. exigua with artificial diets that had been dipped in a series of methoxyfenozide solutions. Larval mortality was recorded at 72 hours after the exposure. The LC50 value of methoxyfenozide for the population from Sanden (Bantu/) was the lowest (0.53 ppm) among 16 tested populations, therefore it was used as reference population to determine the resistance ratio (RR) values of other populations. The RR values of the tested populations variedfrom 1 to 240,8 times. Population collectedfrom Wanasari (Brebes) wasfound to have the highest level of resistance to methoxyfenozide as a result of using methoxyfenozide intensively to S. exigua controlling.